Pengaruh Metode Field Trip Terhadap Hasil Belajar Menulis Argumentasi Siswa Kelas V SD Inpres Tamanyeleng Kab Gowa - Asmaul Husna Ali; Aliem Bahri; Ratnawati Ratnawati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
this study aims to describe the effect of field trip method on the results of learning to write argumentation fifth grade students of SD Inpres Tamanyeleng, Gowa District. This type of research is a pre-experimental research without using a control class that aims to determine the effect of the field trip method on the results of learning to write in the fifth grade students of SD Inpres Tamanyeleng Gowa District. The sample in this study were 21 students. Data collection technique is done by using a test of learning outcomes in the form of pre-test and post-test. Data analysis techniques in this study are descriptive data analysis techniques and inferential data analysis. As for after being given treatment, students have a feeling of pleasure in learning outside the classroom, interest in pouring their ideas in an essay, paying attention to teachers and being actively involved in learning by using field trip learning methods so that writing skills are fulfilled as expected in the application of this learning method. It can be proved from the average score of pretest before treatment obtained 62 is in the low category and the average score on the posttest is 82 is in the high category. So it can be concluded that the Field Trip learning method affects the argumentation writing skills of fifth grade students at SD Inpres Tamanyeleng, Gowa regency.